PENGARUH E-COMMERCE, UANG SAKU, DAN LITERASI KEUANGAN TERHADAP PERILAKU KONSUMTIF MAHASISWA DI MASA PANDEMI COVID-19 - Siti Mubarokah, Martika; Pratiwi, Vivi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Identical consumptive behavior occurs in students because there are abilities and facilities to shop . The purpose of this research is to investigate the effect of e-commerce, pocket money, and financial literacy on the consumptive behavior of students during the coronavirus pandemic. The populace in this study were dynamic understudies of State University of Surabaya, majoring in Accounting Education, amounting to 173 students. A total of 121 students were sampled by purposive sampling. Questionnaires were used as research instruments to obtain respondent data. Data analysis in the form of Multiple Linear Regression through IBM SPSS Statistics 25 for Windows application. The outcomes obtained stated (1) the e-commerce variable had a partial and significant positive effect on the consumptive behavior of understudies . (2) The variable of pocket money affects the consumptive behavior of students positively. (3) Financial literacy has a negative and significant effect on the consumptive behavior of students partially. (4) The variables from e-commerce, pocket money, and financial literacy significantly and simultaneously affect the consumptive behavior of Accounting Education students in corona virus pandemic as much as 72.7%. While several other factors outside the research affect 27.3%.